Investigation of the Views of Biology Teachers on Distance Education during the COVID-19 Pandemic - Ferhat Karakaya; Selcuk Arik; Osman Cimen; Mehmet Yilmaz (Journal of Education in Science, Environment and Health)
Coronavirus disease has caused the death of many people since its first identification in Wuhan, China, in December 2019. Countries have implemented emergency action plans in many areas to prevent the disease from spreading further. In order to reduce the spread of the disease throughout the country, there has been a transition to distance education in the Turkish education system. In this research, it is aimed to determine the views of biology teachers about distance education in COVID-19 Pandemic process. The research using phenomenological study was carried out with 62 biology teachers. Semi-structured interview form prepared by the researchers was used to collect the data. The data were evaluated by using content analysis method. As a result of the research, it has been determined that distance education increases technology use, cooperation, empathy and positive thinking about lessons. However, it has been determined that there are problems arising from the lack of technological infrastructure and knowledge. It has been understood that in order for the distance education systems to be applied in situations such as the COVID-19 pandemic, the technological infrastructure and the knowledge of the stakeholders should be improved.